Effect of Alkaloids Isolated from Phyllodium pulchellum on Monoamine Levels and Monoamine Oxidase Activity in Rat Brain - Cai, Lu (Evid Based Complement Alternat Med, 2016)
Phyllodium pulchellum (P. pulchellum) is a folk medicine with a significant number of bioactivities. The aim of this study was to investigate the effects displayed by alkaloids fractions, isolated from the roots of P. pulchellum, on neurotransmitters monoamine levels and on monoamine oxidase (MAO) activity. Six alkaloids, which had indolealkylamine or β-carboline skeleton, were obtained by chromatographic technologies and identified by spectroscopic methods such as NMR and MS. After treatment with alkaloids of P. pulchellum, the reduction of DA levels (54.55%) and 5-HT levels (35.01%) in rat brain was observed by HPLC-FLD. The effect of alkaloids on the monoamines metabolism was mainly related to MAO inhibition, characterized by IC(50) values of 37.35 ± 6.41 and 126.53 ± 5.39 μg/mL for MAO-A and MAO-B, respectively. The acute toxicity indicated that P. pulchellum extract was nontoxic.